Membangun Keadilan Sosial Di Indonesia Dalam Perspektif Fikih Siyasah - ANNISA PUTRI REZEKI; AHDIAN SYAPUTRA BINTANG; FAHRANI; TRI ANISAH; LAILAN HAFNI GULO (Tabayyun : Journal Of Islamic Studies, 2023)
This research aims to explore the concept and implementation of social justice development from the perspective of Islamic jurisprudence. In analyzing fiqh texts and Islamic siyasa concepts, this research explores the principles that can guide the development of social justice in society. Through research findings, it is hoped that deeper insight can be gained about how the values ​​of justice in siyasah fiqh can be applied in the social context that is currently developing rapidly. In an effort to achieve this goal, researchers will conduct in-depth studies of various important theories and concepts in Islamic jurisprudence and involve various resources to enrich understanding of key issues related to the development of social justice. Researchers will also discuss several concrete cases from the real world to provide examples of how the principles of justice in siyasah fiqh can be implemented effectively in practice. Through this research, it is hoped that a more comprehensive understanding of the concept of social justice development can be obtained from the perspective of siyasah fiqh. It is also hoped that the important findings from this research can contribute to the development of social justice development theory and practice more broadly. As a result, we can strengthen the foundation of human values ​​and morality in our society and advance shared prosperity.